Influence of π–π Stacking Interactions on the Assembly of Layered Copper Phosphonate Coordination Polymers: Combined Powder Diffraction and Electron Paramagnetic Resonance Study - Marco Taddei (Crystal Growth & Design, 2012)
Three new copper phosphonate coordination polymers have been obtained following very soft synthetic routes, and their structures were determined ab initio from powder X-ray diffraction data. They are based on the two building blocks α,α′-m-xylylenediphosphonic and α,α′-p-xylylenediphosphonic acid, either exclusively or combined with 4,4′-bipyridine as an ancillary ligand. The compound obtained from α,α′-m-xylylenediphosphonate has the formula Cu(HO3PCH2)2C6H4·3H2O and a 2D structure of mixed organic–inorganic layers built up by the connection of inorganic chains made of edge-sharing copper octahedra via organic bridging groups. The compound obtained from α,α′-m-xylylenediphosphonate and 4,4′-bipyridine as a coligand has the formula Cu[(HO3PCH2)2C6H4][N(CH)4CC(CH)4N]·2H2O and a 2D structure based on the connection, via the diphosphonic ligand, of the linear chains resulting from the bridging of copper atoms by the bipyridine moieties. The compound obtained using α,α′-p-xylylenediphosphonate and 4,4′-bipyridine as a coligand has the same formula and a 2D structure closely resembling that of the previous compound. The influence of the factors driving the molecular assembly is discussed, pointing out the crucial role played by the 4,4′-bipyridine in promoting the π–π stacking interactions. With increasing temperatures, the compounds revealed a loss of water molecules bound to copper; in particular, heating the copper α,α′-m-xylylenediphosphonate–bipyridine results in a relatively stable phase with unsaturated coordination sites on the metal atoms. This behavior was confirmed by magnetic susceptibility and electron paramagnetic resonance measurements which also provided evidence for a partial reversibility of the dehydration process and of the occurrence of weak antiferromagnetic interactions between Cu(II) ions.